Salem witch trials - Loh-Hagan, Virginia (Loh-Hagan, Virginia. Surviving history., 2021)
Describes aspects of life in Salem, Massachusetts, explaining why some individuals were targeted as witches. Engages the reader in a question-and-answer activity that helps them gauge their survival chances if they were accused of being a witch. Concludes with a glossary, an index, activities, and an author biography.